The second wave of violence scholarship: South African synergies with a global research agenda. (December 2015) - Bowman, Brett; Stevens, Garth; Eagle, Gillian; Langa, Malose; Kramer, Sherianne; Kiguwa, Peace; Nduna, Mzikazi
Abstract: Violence is a serious public health and human rights challenge with global psychosocial impacts across the human lifespan. As a middle-income country (MIC), South Africa experiences high levels of interpersonal, self-directed and collective violence, taking physical, sexual and/or psychological forms. Careful epidemiological research has consistently shown that complex causal pathways bind the social fabric of structural inequality, socio-cultural tolerance of violence, militarized masculinity, disrupted community and family life, and erosion of social capital, to individual-level biological, developmental and personality-related risk factors to produce this polymorphic profile of violence in the country. Engaging with a concern that violence studies may have reached something of a theoretical impasse, 'second wave' violence scholars have argued that the future of violence research may not lie primarily in merely amassing more data on risk but rather in better theorizing the mechanisms that translate risk into enactment, and that mobilize individual and collective aspects of subjectivity within these enactments. With reference to several illustrative forms of violence in South Africa, in this article we suggest revisiting two conceptual orientations to violence, arguing that this may be useful in developing thinking in line with this new global agenda. Firstly, the definition of our object of enquiry requires revisiting to fully capture its complexity. Secondly, we advocate for the utility of specific incident analyses/case studies of violent encounters to explore the mechanisms of translation and mobilization of multiple interactive factors in enactments of violence. We argue that addressing some of the moral and methodological challenges highlighted in revisiting these orientations requires integrating critical social science theory with insights derived from epidemiology and, that combining these approaches may take us further in understanding and addressing the recalcitrant range of forms and manifestations of violence. Highlights: Violence studies has reached a theoretical impasse. Second wave violence scholarship requires new theory to complement epidemiology. Definitions of violence should be revisited and morally situated. Case-based analyses are critical for advancing violence scholarship. Synergies between South African and global violence studies are instructive.